Aplikasi Penjualan Alat Kesehatan Pada Toko Alat Kesehatan Pt Sekarguna Medika Dengan Menggunakan Microsoft Visual Foxpro 9.0 - linda wahyu widianti; hening hendrato; neneng mariana (Liaison Journal of Engineering, 2022)
At this writing the author writes about making a data collection application and presenting information on the sale of medical devices at PT SEKARGUNA MEDIKA which is intended for production managers as a convenience for recording and presenting reports on sales data and inventory data. Sometimes if a data collection still uses manual data processing, it will take a long time. Therefore, an application is needed that can help the production manager process data faster. Therefore, the author makes an application for selling this medical device using Microsoft Visual FoxPro 9.0.Keywords: System, Information, Mark, Student, Internet, PHP, MySQL